Long-distance dispersal and home range establishment by a female sub-adult tiger (Panthera tigris) in the Panna landscape, central India - Sarkar, Mriganka Shekhar; Niyogi, Rajashekhar; Masih, Rebecca Lal; Hazra, Poushali; Maiorano, Luigi; John, Robert (European journal of wildlife research, 2021)
Dispersal from one population to another is crucial for meta-population stability and survival. Long-distance dispersal events have been widely documented in male tigers ( Panthera tigris ), but similar events in female tigers are less known. We opportunistically recorded a long-distance dispersal event that ended with the establishment of a new home-range for a radio-collared sub-adult female tiger in central India. We analysed the animal’s movement patterns during the dispersal event and the subsequent home-range establishment. The average minimum distance and the average minimum daily displacements were 11.4 km and 4.5 km respectively. The total linear and cumulative displacements were 99.1 km and 340.2 km respectively, undertaken over 78 days. Using a Brownian bridge movement model, we showed that the tiger was not moving in a linear path, but showed exploratory movement. During this dispersal event, the tiger traversed an area of 2082 km 2 (95% UD), including 19 distinct ‘stepping-stone’ habitat patches. Combining the Ornstein–Uhlenbeck movement behaviour model and an autocorrelated kernel density estimation model, we identified a newly established home range of 40.3 km 2 at the end of the dispersal event. Our results describe the longest known female tiger dispersal event, highlighting the possibility that natural dispersal of female tigers can provide an additional option to assisted translocations for the species range expansion. This is relevant in current scenarios where tiger habitats remain fragmented and tiger population numbers are recovering due to effective in situ conservation efforts.